2017
DOI: 10.1016/j.physio.2017.11.093
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic dysfunction in whiplash associated disorders: a systematic review

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…posture. This range of presentations is reflected in the epidemiology literature where pain prevalence varies widely (3), is associated with a known condition or disease, or where thoracic pain co-exists with pain in other regions, albeit less severe or secondary to the primary complaint (3,5,6,8).…”
Section: Clinical Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…posture. This range of presentations is reflected in the epidemiology literature where pain prevalence varies widely (3), is associated with a known condition or disease, or where thoracic pain co-exists with pain in other regions, albeit less severe or secondary to the primary complaint (3,5,6,8).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Survey development was informed based on current evidence (5,22,23,29,50), expertise (NH, AR) and comparable surveys (34,38). View and participation rates for the survey were excellent compared to other e-surveys (51).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, a recent systematic review reported that the sternocleidomastoid and scalene muscles are also highly affected by TrPs (48%–65%) in patients with whiplash-associated neck pain. 7 However, no clear data about the presence and relevance of TrPs in the scalene muscles are available in mechanical neck pain. 6…”
Section: Introductionmentioning
confidence: 99%